Decomposition analysis of economic growth in Afar region, Ethiopia - Getachew Wollie Asmare (Cogent Economics & Finance, 2022)
This paper is aimed to decompose, the economic growth of the Afar national regional state of Ethiopia in to labor productivity, employment rate and working age population and to verify whether the positive economic growth registered earlier on the region was a job creation growth or not. To do so, annual time series data ranging from 2010 to 2018 were used and per capita value added as a measure of economic growth was decomposed by using Shapley decomposition analysis technique. The result reveals that changes in output per worker accounted the highest proportion (74.33%) followed by changes in working age population (32.85%) and employment rate (-7.17%) for the total change in per capita value added during the entire period of time. The negative growth changes registered in employment rate implied that the economic growth registered on the Afar national regional state was a jobless growth. The economic growth patterns of Afar region does not favor the agriculture sector where the poor are found. The within-sector takes the lion share contributing (72.67%) to aggregate change in output per worker growth followed by structural change (13.21%) and interaction of within sectors and structural change (14.11%). Finally, these findings navigated us to suggest for policymakers, to amend their sector-wise economic policies and strategies focused to enhance employment generation and labor productivity of the Afar region.
Keywords: 330; Value added; structural change; decomposition analysis; Ethiopia